2001
DOI: 10.1248/bpb.24.351
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Phytoestrogens with Estrogen Receptors .ALPHA. and .BETA..

Abstract: The human estrogen receptor (hER) exists as two subtypes, hER a a and hER b b, that differ in the C-terminal ligand-binding domain and in the N-terminal transactivation domain. In this study, we investigated the estrogenic activities of soy isoflavones after digestion with enteric bacteria in competition binding assays with hER a a or hER b b protein, and in a gene expression assay using a yeast system. The estrogenic activities of these isoflavones were also investigated by the growth of MCF-7 breast cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
381
2
20

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 569 publications
(425 citation statements)
references
References 36 publications
22
381
2
20
Order By: Relevance
“…This association may be mediated by oestrogenic and/or a number of anti-carcinogenic properties, although the biological effects of exposure to phyto-oestrogens in humans remain uncertain (Bingham et al, 1998;Magee and Rowland, 2004;McCann et al, 2005;McCormick et al, 2007). Phyto-oestrogens have a structure similar to mammalian oestrogens and can bind to the oestrogen receptor (Morito et al, 2001;Mueller et al, 2004). Experimental evidence suggests that the interaction of isoflavones with the oestrogen receptor beta (ER-b) might be particularly important in the development of prostate cancer (Morito et al, 2001;McCarty, 2006); compared with daidzein, genistein has a much greater affinity for the ER-b, selectively promoting ER-b signalling which in turn may suppress cellular proliferation and promote differentiation in the prostate (McCarty, 2006;Ricke et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association may be mediated by oestrogenic and/or a number of anti-carcinogenic properties, although the biological effects of exposure to phyto-oestrogens in humans remain uncertain (Bingham et al, 1998;Magee and Rowland, 2004;McCann et al, 2005;McCormick et al, 2007). Phyto-oestrogens have a structure similar to mammalian oestrogens and can bind to the oestrogen receptor (Morito et al, 2001;Mueller et al, 2004). Experimental evidence suggests that the interaction of isoflavones with the oestrogen receptor beta (ER-b) might be particularly important in the development of prostate cancer (Morito et al, 2001;McCarty, 2006); compared with daidzein, genistein has a much greater affinity for the ER-b, selectively promoting ER-b signalling which in turn may suppress cellular proliferation and promote differentiation in the prostate (McCarty, 2006;Ricke et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Phyto-oestrogens have a structure similar to mammalian oestrogens and can bind to the oestrogen receptor (Morito et al, 2001;Mueller et al, 2004). Experimental evidence suggests that the interaction of isoflavones with the oestrogen receptor beta (ER-b) might be particularly important in the development of prostate cancer (Morito et al, 2001;McCarty, 2006); compared with daidzein, genistein has a much greater affinity for the ER-b, selectively promoting ER-b signalling which in turn may suppress cellular proliferation and promote differentiation in the prostate (McCarty, 2006;Ricke et al, 2007). It is unclear though whether the levels of dietary phyto-oestrogen exposure in humans are sufficiently high to exert a biological effect (Liggins et al, 2000b;McCarty, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that equol excretors are in the minority (Rowland et al, 2000). The interest in equol derives partly from the fact that equol binds to oestrogen receptors with greater affinity than its parent compound formononetin and equally with that of genistein (Morito et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The binding affinity of equol for estrogen receptors has been found to be similar to that of other isoflavones, but equol induced transcription more strongly than did any other isoflavone. 18) The present study did not determine the target cells and mechanism by which equol perpetrated colitis. However, this study has shown for the first time that a soy isoflavone regulated the inflammatory response in the intestines.…”
mentioning
confidence: 74%